An exploratory study of decentralised shopping in Singapore. - Chua, Dan Kok Leong. (2013)
This project has been conceived out of a desire to learn more about consumer shopping behaviour in Singapore which is a relatively unexplored area of research in this part of the world. Specifically, the exploratory study examines how Singaporean shoppers respond to the newly-built major retailing centres in the suburbs; the recently- opened Tiong Bahru Plaza is used as the focal model for this retail study.